Isolation and characterization of mutants impaired in the selective degradation of peroxisomes in the yeast Hansenula polymorpha. - Titorenko, V I (1995)
We have isolated a collection of peroxisome degradation-deficient (Pdd-) mutants of the yeast Hansenula polymorpha which are impaired in the selective autophagy of alcohol oxidase-containing peroxisomes. Two genes, designated PDD1 and PDD2, have been identified by complementation and linkage analyses. In both mutant strains, the glucose-induced proteolytic turnover of peroxisomes is fully prevented. The pdd1 and pdd2 mutant phenotypes were caused by recessive monogenic mutations. Mutations mapped in the PDD1 gene appeared to affect the initial step of peroxisome degradation, namely, sequestration of the organelle to be degraded by membrane multilayers. Thus, Pdd1p may be involved in the initial signalling events which determine which peroxisome will be degraded. The product of the PDD2 gene appeared to be essential for mediating the second step in selective peroxisome degradation, namely, fusion and subsequent uptake of the sequestered organelles into the vacuole. pdd1 and pdd2 mutations showed genetic interactions which suggested that the corresponding gene products may physically or functionally interact with each other.